Mulheres na licenciatura: um olhar para as docentes da Universidade Federal do Pampa - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This paper presents an analysis of the academic, professional and personal journey of five female college professors of the Federal University of Pampa. The analysis of an online survey answered by the professors guided to the understanding of the reasons why these women chose the licenciature carrer, which one is strongly considered a feminine field, in addition to showing aspects that make the university an athmosphere that transmits differences between genders. Also, this research collected quantitative data on the number of female and male professors by their field of study, showing that there is still a gender division in certain fields of study at the University.
Women in the degree: a look at the professors of the Federal University of Pampa
Keywords: Mulheres; Gênero; Woman; Gender; Science Education; Learning; Educação; PIBID; Aprendizagem; Ciências da Natureza; CNPQ::CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM